Pemanfaatan Gamma AI Sebagai Media Pendukung Pembuatan Presentasi Digital dalam Meningkatkan Literasi Teknologi Siswa SMK - Soliman Syafii; Stalifa Ayu Sindidu; Camelia Savitri (Universitas Hamzanwadi, 2025)
The utilization of Artificial Intelligence (AI) in education continues to expand, including through platforms such as Gamma AI, which supports automatic, structured, and time-efficient digital presentation creation. This activity aims to improve technological literacy among students of SMK Negeri 1 Arosbaya through training on the use of Gamma AI as a supporting tool for developing digital presentations. The method consists of needs analysis, training, hands-on practice, evaluation, and reflection. A total of 25 students from the Computer and Network Engineering program participated in this activity. The results indicate an improvement in students’ ability to create more structured, engaging, and informative presentations compared to their previous work prior to training. Based on the questionnaire responses, 87% of students reported that Gamma AI significantly helped accelerate the presentation-making process, while 13% required additional adaptation time. These findings demonstrate that Gamma AI is effective as a learning support tool and can enhance students' creativity and technological literacy skills. Therefore, the implementation of Gamma AI serves as an innovative solution to support students in producing high-quality digital content and encourage technology-based learning habits in schools.